Digitalisasi Pemasaran Produk Tenun Ikat melalui Platform E-Commerce bagi Perajin di Desa Nita, Kabupaten Sikka, Nusa Tenggara Timur - Yolanda Mering Siu; Alberthina Hoi Betan; Kornelius Watu (Lembaga Publikasi Ilmiah Nusantara, 2026)
Ikat weaving is one of the prominent cultural products of East Nusa Tenggara with strong economic and local identity values. However, many rural artisans still face marketing challenges due to limited digital technology adoption, restricted market access, and insufficient capability in managing online promotional strategies. This community service program aimed to improve the capacity of ikat weaving artisans in Nita Village, Sikka Regency, through the implementation of digital marketing based on e-commerce platforms. The program methods included partner needs assessment, digital marketing training, product catalog development assistance, optimization of social media and e-commerce platforms, and evaluation of participants’ capabilities after the program. The results showed improved artisans’ understanding of digital marketing strategies, product content management, basic product photography techniques, and the use of digital platforms to expand market reach. In addition, artisans were able to develop product identities through cultural storytelling approaches that increased the attractiveness of ikat weaving promotion. The implementation of digital marketing provides opportunities for artisans to improve consumer access, strengthen business sustainability, and enhance the competitiveness of local ikat weaving products in broader markets.